Study of the seed protein composition and the amplification of the cytosolic chaperonin gene from some soybean cultivars of the North-West mountainous region, Vietnam - Mau, Chu Hoang; Thanh Huong, Le Thi; Hung, Nguyen Phu; Long, Tran Dinh (Academia Journal of Biology, 2014)
The seeds of some soybean cultivars of the North-West mountainous region, Vietnam (vang Muong Khuong, azuki, Bat Xat, Ha Giang, xanh Bac Ha, AK06, Cuc vang, DT12, DT93, Lo 75 and M54) were used to study of the seed protein composition and the amplification of the cytosolic chaperonin gene; among them, the vang Muong Khuong, azuki, Bat Xat-Lao Cai, Ha Giang and xanh Bac Ha cultivars were local ones. These seeds were used to extract lipid and storage proteins. The total protein content in the seeds of these soybean cultivar was from 18.87 - 22.80% of dry weight and this value was highest in the xanh Bac Ha cultivar (22.80%). The total lipid content was from 5.78 - 24.17% of dry weight and especially the azuki cultivar had the lowest lipid percentage (5.78%). The seed protein fractions of some soybean cultivars were analyzed by 12.5% - SDS polyacrylamide gel electrophoresis. The analytic result showed that the storage proteins of some local soybean cultivars had the polymorphism. Especially, the result showed the difference in b-conglycinin and glycinin subunits distribution of the azuki cultivar in comparison with other cultivars. The total genomic DNAs from the soybean seedlings have been isolated. The cytosolic chaperonin gene was amplified by polymerase chain reaction (PCR) with the molecular weight about 1.6 kb from five soybean cultivars.